Effect of Magnetic Fields on Equatorial Circular Orbits in Kerr Spacetimes - Ranea Sandoval, Ignacio Francisco (2012)
In this work we analyze the effects of an external magnetic field on charged particles on equatorial circular orbits in a Kerr spacetime, both in the black hole and the naked singularity cases. Understanding these phenomena is of great importance because equatorial circular orbits are a key ingredient of simple accretion disc models. We focus on two important magnetic field configurations: (a) a uniform magnetic field aligned with the angular momentum and (b) a dipolar magnetic field. We center our attention on the effect of these external fields on the marginally bound and marginally stable equatorial circular orbits because they give information on observable quantities that could be useful to determine whether the central object is a black hole or a naked singularity. Using a perturbative approach we are able to give analytic results and compare (in the black hole case) with previous results.